Spatial–temporal evolution and influencing factors of urban–rural economic circulation in China’s agricultural areas: A case study of Jianghan Plain - Xiaoyue Li (PLoS ONE, 2025)
Urban–rural economic circulation (UREC) is an important part of the domestic economic circulation and an important element in the construction of the new development paradigm of “dual circulation” in China today. Currently, the uneven development of UREC in China threatens the sustainable development of the urban–rural economy. Quantitative research on UREC is lacking in the academic community. As a result, research at the national level cannot easily provide guidance in agricultural regions. Therefore, theoretical and case-based empirical research on UREC must be carried out urgently. This study proposes a theoretical framework and a measurement index system for UREC. It uses the Jianghan Plain, a traditional agricultural growing area in China, as a case study. It also uses the entropy method and stepwise regression analysis to study the spatiotemporal evolution of UREC and the influencing factors from 2013 to 2020. Results show that, from 2013 to 2020, the UREC index of the Jianghan Plain grew year by year, and the spatial difference increased. Regional administrative power and urban–rural socioeconomic development levels had a significant impact on UREC in the Jianghan Plain, with general public budget expenditures having the greatest positive impact.